Penerapan Audit Internal Terpadu dalam Sistem Manajemen Terpadu Berdasarkan PAS 99:2012 Di Industri Perisa - Pika Mustika; Lilis Nuraida; Harsi Dewantari Kusumaningrum (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Individually implementation of management system standard of quality (ISO 9001), food safety (FSSC 22000), and halal assurance (HAS 23000) require a lot of resources in a food company. This study aimed to develop perangkat of internal audit (IA) by integrating the three standards into an Integrated Management System (IMS) based on the management system requirements framework, PAS 99:2012. The study was started by integrating all the major requirements of standards follows the Deming's PDCA cycle approach consisting of 7 clauses. The perangkat of IA was developed based on the IMS and implemented in PT IBP. Evaluation the effectiveness of the perangkat of IMS IA is done by analyzing the gap of IA results with external audit results. For integration of the standards, the most standard used as a case of IMS was the standard of FSSC 22000. The result of IA using the developed perangkat of IA was in agreement with the result of external audit. This suggest that the integration of the audit system has adequately covered all requirements based on the 3 standards. In addition, there is an opportunity to improve the ability of internal auditors in assessing the conformity of the implementation of planning.